Employee Productivity in Start-ups in Jakarta: Digital Transformation, Work-Life Balance, and Diversity - Asyhari, Sri Irmayanti (West Science Interdisciplinary Studies, 2025)
This study discusses digital transformation, work-life balance, and diversity policy as factors affecting the productivity of employees in startup companies. The research method was Quantitative with data taken from 175 respondents by providing them with a structured questionnaire on a scale ranging between 1-5 for the Likert Scale option. The method used is SEM-PLS 4. This becomes evident from the results that digital transformation, work-life balance, and diversity policy are the top predictors of decreasing order for employees' productivity. Such findings also emphasize the strategic importance of intervention in technology adoption and enabling a balanced work culture in facilitating organizational performance. The findings also contribute to theory and practice by providing actionable insights to leaders in the startup ecosystem in Jakarta.